Effectiveness of Mindfulness on Decreasing Stress in Health Professional Students: A Systematic Review - Akhmad Yanuar Fahmi; Meidiana Dwidiyanti; Diyan Yuli Wijayanti (Holistic Nursing and Health Science, 2018)
Background: Stress in health professional students is increasing every year. Therefore it is necessary to implement stress management for the students. Mindfulness is an alternative which can be used to deal with stress.  Purpose: The purpose of this systematic review is to describe the effectiveness of mindfulness on decreasing stress in health professional students. Methods: This systematic review was conducted by searching relevant articles published in online databases EBSCO, Science Direct, PubMed, and Google. The search was restricted to the full-text articles published in 2010-2017 and employed the RCTs and non-RCTs research designs with a mindfulness intervention.Results: Of the ten articles reviewed, it was found that mindfulness could decrease stress in professional health students with a very significant p-value. The types of mindfulness administered to the health professional students included yoga therapy, MBSR therapy, and meditation therapy. In average, MBSR therapy is used for health professional students. This intervention is practiced through meditation which lasts for 5-35 minutes for 3-6 weeks. Conclusion: The study reported that, in average, the intervention to decrease stress in health professional students is performed by using MBSR with a meditation of 5-35 minutes. The intervention is done for 3-6 weeks. Results found that MBSR mindfulness could decrease stress. Further research is needed to explore the effectiveness of mindfulness on other subjects such as students who get scholarships.